Proposed business strategy for pt.prama anugerah bahana in propoerty business - Aziiz Priojudanto, Alvino; Hamsal, Mohammad (The Indonesian Journal of Business Administration, 2019)
Abstract - PT. Prama Anugerah Bahana is a company engaged in property developer, especially for residential. The company was established in 2015 and has handled a housing project namely Pesona Pabuaran. Currently working on the second project, namely Pesona Jatibening since 2017. Based on the report of the Residential Property Price Survey issued by Bank Indonesia, the growth in sales and housing prices in 2018 has decreased. This also happened to PT. Prama Anugerah Bahana because no single house has been sold after a year on the Pesona Jatibening project. The purpose of this study is to analyze the internal and external environment of property business, to determine the ideal business strategy for PT. Prama Anugerah Bahana, and to develop implementation plan of the new business strategy. Data obtained using qualitative methods by conducting interviews with property stakeholders. Furthermore, several tools are used to analyze the property industry environment. For external analysis used PESTLE analysis, Porter 's Five Forces, and Competitor Analysis. While for internal analysis using Value Chain, VRIO Analysis, Customer Persona, and Existing Business Model Canvas. The next is the formulation of business strategy using SWOT Analysis, Porter Generic Strategies and Diamond Framework Strategy analysis. After environmental analysis and strategy formulation, the business strategy turns into a low-cost focus. Because the condition of Pesona Jatibening does not have sufficient differentiation and competitive advantages around the location. The implementation plan of the business strategy carried out from a financial perspective is to reduce house prices and increasing the marketing fee. While in terms of marketing is to use marketing agents exclusively coupled with large incentives. Keywords: business strategy, property, pestle, porter's five forces, value chain, vrio, porter generic strategies, strategy diamond framework, low-cost focus